Prognostic differences among the positive surgical margin locations following robot-assisted radical prostatectomy in a large Japanese cohort (the MSUG94 group). (27th January 2023) - Sasaki, Takeshi; Ebara, Shin; Tatenuma, Tomoyuki; Ikehata, Yoshinori; Nakayama, Akinori; Kawase, Makoto; Toide, Masahiro; Yoneda, Tatsuaki; Sakaguchi, Kazushige; Teishima, Jun; Makiyama, Kazuhide; Kitamura, Hiroshi; et al.
Abstract: Background: To investigate whether subgroups of prostate cancer patients, stratified by positive surgical margin locations, have different oncological outcomes following robot-assisted radical prostatectomy. Methods: A retrospective multicenter cohort study in prostate cancer patients undergoing robot-assisted radical prostatectomy was conducted at 10 institutions in Japan. Pre- and post-operative outcomes were collected from enrolled patients. Biochemical recurrence and clinical and pathological variables were evaluated among subgroups with different positive surgical margin locations. Results: A total of 3195 patients enrolled in this study. Data from 2667 patients (70.1% [ N = 1869] with negative surgical margins and 29.9% [ N = 798] with positive surgical margins based on robot-assisted radical prostatectomy specimens) were analyzed. The median follow-up period was 25.0 months. The numbers of patients with apex-only, middle-only, bladder-neck-only, seminal-vesicle-only and multifocal positive surgical margins were 401, 175, 159, 31 and 32, respectively. In the multivariate analysis, PSA level at surgery, pathological Gleason score based on robot-assisted radical prostatectomy specimens, pathological T stage, pathological N stage and surgical margin status were independent risk factors significantly associated with biochemical recurrence-free survival. Patients undergoing robot-assisted radical prostatectomy with multifocal positive surgical margins and seminal-vesicle-only positive surgical margins were associated with worse biochemical recurrence-free survival than those with apex-only, middle-only and bladder-neck-only positive surgical margins. Patients undergoing robot-assisted radical prostatectomy with apex-only positive surgical margins, the most frequent positive surgical margin location, were associated with more favorable biochemical recurrence-free survival that those with middle-only and bladder-neck-only positive surgical margins. The study limitations included the lack of central pathological specimen evaluation. Conclusions: Although positive surgical margin at any locations is a biochemical recurrence risk factor after robot-assisted radical prostatectomy, positive surgical margin location status should be considered to accurately stratify the biochemical recurrence risk after robot-assisted radical prostatectomy. Abstract : This large Japanese cohort study showed that while positive surgical margin (PSM) at any locations is a biochemical recurrence risk factor after robot-assisted radical prostatectomy, apex-only PSMs had more favorable outcome.